PENERAPAN KOMBINASI ALGORITMA OTP DAN RSA PADA FILE GAMBAR - Meliala, Evan Syahputra; Fira Dwi Yanti; Anggi Meliana Br Hutasoit; Sri Defriani Br Sembiring; Achmad Fauzi (Jurnal Sistem Informasi Kaputama (JSIK), 2025)
This study discusses the application of a combination of the One-Time Pad (OTP) and Rivest-Shamir-Adleman (RSA) algorithms to enhance data security in image files. The combination of these two algorithms offers higher security, with OTP used to encrypt image data with unique random keys, and RSA employed to securely encrypt the OTP key. This method leverages the strengths of each algorithm, namely OTP's mathematical security and RSA's key distribution capability. The results of the study indicate that this combination is effective in protecting image files from cryptographic threats, although challenges remain in terms of efficiency and compatibility with certain data formats. Keywords : Cryptography, OTP Algorithm, RSA Algorithm, Image file encryption, Data security, Hybrid encryption.